The Role of Soil Water Solutes Type on Changes in Evaporation Intensity from sandy and clayey soils - M.R. Shoaibi Nobariyan; M.H. Mohammadi (علوم آب و خاک, 2025)
The objective of this study is to investigate the effects of solutes and water quality on evaporation amount and rate in two sandy and clayey soils. Soil samples containing aggregates and sand particles with diameters ranging from 0.5 to 1 millimeter were collected. Six columns were prepared during the experiment; three columns were filled with sandy soil and three with aggregated soil, each measuring 60 cm in height and 15.5 cm in inner diameter. One reference column was filled with distilled water. A saturated calcium sulfate solution was added to two columns, a 0.01 molar calcium chloride solution was added to two other columns, and distilled water was added to the remaining two. The amount of water lost through evaporation was recorded every 8 to 12 hours by weighing the columns. After approximately 130 days, the columns were sectioned, allowing for the establishment of moisture and solute concentration profiles for each soil column. The results indicated that the first and second stages of evaporation were distinguishable in sandy soil, whereas in clayey soil (aggregated soil), only the first stage of evaporation occurred due to the gradual transfer of water and the continuous hydraulic connection from the surface to the water table. The presence and type of solutes affected the evaporation rate and moisture profile, reducing evaporation and increasing water retention in deeper soil layers. Hydraulic connectivity (calcium sulfate > calcium chloride > distilled water) and the resulting capillary rise of and supply of evaporated water from higher layers caused a greater evaporation rate in the calcium sulfate compared to the calcium chloride and distilled water treatments in both soil types. Additionally, the formation of a salt crust on the soil surface due to solutes disrupted the hydraulic connection with the surface, resulting in decreased evaporation rates and cumulative evaporation.